Reģionālās vides pārvaldības attīstība: sadarbības pārvaldības pieeja - Zvirbule, Līga (Latvijas Universitāte, 2012)
Lai sekmētu reģionālo valsts institūciju un pašvaldību sadarbību vides pārvaldībā, ir izstrādāts magistra darbs ,,Reģionālās vides pārvaldības attīstība: sadarbības pārvaldības pieeja”. Pētījuma ietvaros ir veiktas 3 gadījumu izpētes, 12 daļēji strukturētās dziļās intervijas, reģionālās vides pārvaldes un pašvaldību funkciju salīdzinošā analīze. Pētījuma rezultātā ir izstrādātas Sadarbības pārvaldības vadlīnijas reģionālās vides pārvaldības attīstībai. Darbā ir 8 nodaļas, kas ietver 140 lapaspuses. Atslēgas vārdi: sadarbības pārvaldība, reģionālā vides pārvaldība, vides pārvaldības attīstība .

To promote the regional government institutions and municipalities collaborative in environmental governance, is designed Master Paper ,,Regional environmental governance development: collaborative governance approach”. The study is carried out three cases studies, 12 partly structured in – depth interviews, regional government institutions and municipalities functions of comparative analysis. The study led to the development of collaborative governance guidlines for the development of regional environmental governance. The Paper has 8 chapters, covering 140 pages. Keywords: regional environmental governance, collaborative governance, environmental governance development.
Regional Environmental Governance Development: Collaborative Governance Approach
Keywords: Vides pārvaldība